Scholasticism versus Discovery in Kinship Studies: Review of Maurice Godelier’s The Metamorphoses of Kins - Shapiro, Warren (Anthropologica, 2015)
Maurice Godelier’s supposedly comprehensive treatment of kinship studies is in fact decidedly truncated: it derivesless from an earnest concern with kinship as a human phenomenon and more from established conventions of textbook writing. In particular, it overemphasizes typologies derived from alliance theory and descent theory and, at the same time, pays almost no attention to real discoveries, particularly concerning kinship semantics and the genesis of incest taboos.